Smart Window Puzzle as An Innovative Learning Media: Its Impact on Student Learning Outcomes in Vocational High Schools - Azizah, Nurul; Wicaksono, Megan; Isyarafi, Haziq Fardha (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study aims to examine the effectiveness of the Smart Windows Puzzle learning media in improving learning outcomes in Islamic Education at Al Basyariyah Vocational High School. The study is motivated by the monotonous learning models applied in the classroom, which focus only on cognitive outcomes and ignore affective and psychomotor domains, despite students' relatively good cognitive performance. A quantitative method was used with a True Experimental Design in the form of a Pretest-Posttest Control Group Design. The sample consisted of 50 eleventh-grade students, with 24 in the experimental group and 26 in the control group. Data were collected through posttests and analyzed using IBM SPSS v27.0. The Mann Whitney U Test was applied due to non-normal data distribution. The results showed that the experimental group scored higher (89.58) than the control group (78.85), with a significance value of 0.000 < 0.05, indicating a significant effect. Therefore, the Smart Windows Puzzle media is proven effective in enhancing Islamic Education learning outcomes. This research is expected to guide teachers in implementing innovative strategies and learning media in integrating Islamic values into vocational education.